Congenital oesophageal stenosis. Issue 5 (May 1977) - Valerio, D; Jones, P F; Stewart, A M
Abstract : A case of congenital oesophageal stenosis presenting shortly after birth is reported. Treatment by daily dilatation with a bead on a continuous thread loop was carried on at home over several months. This proved to be a simple, safe, and effective treatment.